Design of a Situation Aware Service for Internet of Things - Im Y. Jung; Gil-Jin Jang; Jung-Min Yang; Jaesoo Yoo (International Journal of Distributed Sensor Networks)
The Internet of Things (IoT) operates solely on local interactions among its components, which include various devices with communications capabilities. Because the IoT is a fully distributed computing network, it is important to mitigate any negative effects resulting from faults occurring in its components and to provide sustainable services. This paper focuses on fault management of IoT services. In particular, it handles a fault management scheme for the self-organizing software platform (SoSp), a platform on which IoT services connected to various IT devices are deployed. The proposed fault management scheme enables SoSp to provide situation aware IoT services without loss of data and state.